2021
DOI: 10.1111/ijcp.14214
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of various drugs used for medical expulsive therapy for distal ureter stones: A systematic review and network meta‐analysis

Abstract: Objectives Medical expulsive therapy has been found to be effective for distal ureteric stones; however, which drug is most efficacious in terms of stone expulsion rate (SER) and stone expulsion time (SET) is not known. With this review we aimed to compare the efficacy of various drug treatments for distal ureter stones used as medical expulsive therapy in terms of SER and SET. Methods Systematic literature search was conducted to include all the randomised study comparing various drug interventions for lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 73 publications
0
11
1
Order By: Relevance
“…The patients administered with tamsulosin and naftopidil reported a worsening of health condition than those receiving silodosin. These findings suggest that silodosin may have an added advantage in management of LUTS after 125 I prostate brachytherapy compared with other α 1 -blockers. 116 A pressure flow study to check the urodynamics of silodosin treatment revealed a significantly enlarged bladder capacity when first non-voiding contraction was seen at 3 and 12 months (3M: 127.1 ± 74.8 vs 118.2 ± 83.9 mL, P = 0.001; 12M: 123.7 ± 79.3 vs 100.3 ± 73.4 mL, P = 0.01).…”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…The patients administered with tamsulosin and naftopidil reported a worsening of health condition than those receiving silodosin. These findings suggest that silodosin may have an added advantage in management of LUTS after 125 I prostate brachytherapy compared with other α 1 -blockers. 116 A pressure flow study to check the urodynamics of silodosin treatment revealed a significantly enlarged bladder capacity when first non-voiding contraction was seen at 3 and 12 months (3M: 127.1 ± 74.8 vs 118.2 ± 83.9 mL, P = 0.001; 12M: 123.7 ± 79.3 vs 100.3 ± 73.4 mL, P = 0.01).…”
Section: Methodsmentioning
confidence: 81%
“… 124 The same researchers reported that a tadalafil plus silodosin combination and silodosin as an individual drug are the best for treating lower ureter stones considering the SET and SER. 125 A meta-analysis carried out by Liu et al reported similar findings stating that tadalafil plus silodosin has the highest probability of reducing SET, and treating ureteral stones ≤10 mm. 126 …”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…The reason for a similar expulsion rate between silodosin and tamsulosin in our study may be due to the use low dose of silodosin. On the other hand, two recent meta-analyses found that the combination of different drugs was shown to be superior to the use of individual agents such as MET (8,23). The possible explanation for a higher success rate in combination therapy may be due to the different and more mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…Although alpha-antagonists have been shown by meta-analyses to have an impact on MET [48][49][50], large placebo-controlled, double-blinded RCTs have not been able to show any significant benefits in various scenarios except for stones >5 mm in the distal ureter [51][52][53][54][55]. A recent systematic review and meta-analysis revealed that there was no significant difference in the effectiveness of calcium-channel inhibitor or PDEI5 monotherapy when compared to placebo; however, the combination proved to be effective mainly for distal ureter stones [56]. The 2023 EAU guidelines recommend alpha-antagonists for MET for distal ureteral stones larger >5 mm, however they are not specifically advised for elderly patients [11].…”
Section: Conservative Treatmentmentioning
confidence: 99%